(untitled) (Journal of Partial Differential Equations, 1996)
This paper deals with a class of strongly coupled and highly degenerate nonlinear parabolic systems, which arises from a model describing non-Fickian diffusion of penetrant into glassy polymers. By means of a fixed point argument and a priori estimates, we establish the global existence and uniqueness for the systems.